Pertumbuhan dan Biomassa Spirulina sp dalam Skala Laboratoris - Hariyati, Riche - (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2008)
Spirulina is unicelular algae used as a natural food of brawn shrimp and fish larval that has high nutritionalvalve. The aims of this research is to asses growth and biomass of spirulina sp at laboratorium scale. Method wascarried out by culturing Spirulina sp using walne culture media.The density of Spirulina sp was conuted for 9 days . The result of this research shows that optimal densitycuhich was 11.698.103 unit/ml occurred on the day 7th with wet weight was o,042 gr/l and dry weight was 0,0375gr/l. Spirulina biomass an increased as a responsive of their growth at a certain level